1995
DOI: 10.1007/bf02542070
|View full text |Cite
|
Sign up to set email alerts
|

Wetting of fat crystals by triglyceride oil and water. 1. The effect of additives

Abstract: Wetting of fat crystals has been extensively examined in this work by contact angle (0) measurements of fat crystal, oil, and water in three-phase contact. Contact angle was measured in oil. The crystals were nonpolar and wetted by oil for a contact angle equal to 0 °, and polar and wetted by water for an angle equal to 180 °. Fat crystals are expected to contribute to the stability of margarine emulsions if they are preferentially wetted by the oil phase (0 ° < 0 < 90°), but result in instability if they are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
34
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(34 citation statements)
references
References 11 publications
0
34
0
Order By: Relevance
“…Although the impact of fat crystals on emulsion stability has previously been investigated Johansson et al, 1995b;Krog and Larsson, 1992;van Boekel and Walstra, 1981), there has been only one attempt, to our knowledge, to test the stability of emulsions containing fat crystals against salt release under an osmotic pressure gradient (Guery et al, 2009). In their work, the release of chloride ions through a completely solid oil phase was investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Although the impact of fat crystals on emulsion stability has previously been investigated Johansson et al, 1995b;Krog and Larsson, 1992;van Boekel and Walstra, 1981), there has been only one attempt, to our knowledge, to test the stability of emulsions containing fat crystals against salt release under an osmotic pressure gradient (Guery et al, 2009). In their work, the release of chloride ions through a completely solid oil phase was investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Natural surfactants present in bitumen combine with fine clay solids to produce emulsions which hinder the recovery of bitumen from oil sands [6,7]. The interactions between fat crystals and phospholipids or proteins can either stabilise or destabilise food emulsions [8][9][10]. Thus it is necessary to investigate how the addition of surfactants (and polymers) affects Pickering emulsions.…”
Section: Introductionmentioning
confidence: 99%
“…[69][70][71][72][73] These authors also paid special attention to the wettability of fat crystals by oil and water and the various parameters that can affect it. [74][75][76] In an attempt to characterize the effect of emulsifiers on the fat crystal wettability, Johansson and Bergensthål first showed that the different polymorphs were wetted differently; the b polymorph consists of tight TAG molecules that create non-polar surfaces (only wetted by oil) while a and b 0 form crystals are slightly more polar due to looser packing (wetted by both liquids). Crystal wettability can be tailored by adding oil-soluble emulsifiers; in particular, increasing the hydrophiliclipophilic balance (HLB) of the surfactants increases the fat crystal affinity for water.…”
Section: Lipid Particlesmentioning
confidence: 99%